Franz Rosenzweig’s Philosophy of Existence - Freund, E.R. author. aut Link
VIII, 189 p.
Keywords: The Star of Redemption, * which presents Franz Rosenzweig's system of philosophy, begins with the sentence "from death, (vom Tode) , from the fear of death, originates all cognition of the All" and concludes with the words "into life. " This beginning and this conclusion of the book signify more than the first and last words of philosophical books usually do. Taken together - "from death into life" - they comprise the entire meaning of Rosenzweig's philosophy. The leitmotif of this philosophy is the life and death of the human being and not the I of philosophical idealism, where man ultimately signifies "for ethics" no more than" . . . a point to which it (ethics) relates its problems, as for science also he (man) is only a particular case of its general laws. "l Rosenzweig deals with the individual's actual existence, that which is termi nated by death; he speaks of the individual's hic et nunc, of his actions and decisions in the realm of concrete reality. This philosophy is not an exposition of theoretical principles. It is not concerned with man in general in abstract time, but rather with the individual human being, designated by a proper name, living in his particular time. ** Human existence in its finiteness and temporalness forms the focus in which Rosenzweig's motif can be gathered together.